Chemical Pulps for Writing and Printing Papers from Erythrina variegata Linn. var. variegata - Karira, B. G. (Indian Forester, 1977)
Laboratory experiments on the production of chemical pulps from Erythtrina variegata var. variegata for writing and printing papers by the sulphate process are described. The average fibre length of the pulp was 1.38 mm and average fibre diameter was .018 mm. Easy bleaching pulps in good yield with satisfactory strength Properties could be prepared under suitable conditions of digestions.